Analysis of soil penetration resistance in fruit orchards: An overview - ADAK, TARUN; PANDEY, G.; RAJAN, S. (Journal of Soil and Water Conservation, 2020)
Evaluation of penetration resistance in orchard soils is one of the essentially important soil physical indicators for designating the poor or good horticulture practices existed for successful fruit production and commercial business. This is particularly important under precision farming centers of the world for the betterment of economic returns and sustainability. The strength of the soil determines the ease of not only establishment of trees, grasslands, forest samplings, agroforestry, forage crops etc. but also their survivability. Root architecture, distribution (vertical and horizontal), volume, amount, longevity, rate of decomposition etc. and water-nutrient dynamics in totality affected by the soil strength/penetrating resistance in vast range of soils. Soil penetration resistances is influenced by a large number of factors ranging from compaction, organic management, tillage and other factors and are associated with the soil loss, water erosion and conservation related issues. The present analysis showed the variability of penetration resistance across ecological services and its effects on orchard diversity.